Low altitude balloon IoT tracker - Mirza, Mohamed; Ahmad, Yasser Asrul; Gunawan, Teddy Surya (2017)
Low altitude balloon provides a unique and low-cost experiment results to carry out mission in space explorations such as space research study, weather sensing, aerial images, live space videos, surveillance or communication operations. The flight location can be tracked by commercial tracker equipped with existing technology such as satellite-based tracking, cellular phone tracking, APRS system and using Ultra High-Frequency narrow band FM transmitter. These tracking methods are expensive and not interactive in real time to the end user. Sometimes, the balloon get disappears due to natural disaster or communication errors. In order to increase the efficiency and to replace the traditional tracking methods in low altitudes flight tracking, this paper presents an Internet of Things (IoT) based GPS tracking solution for low altitude balloon in real-time. This implementation used Low Power Wide Area (LPWA) Network by deploying Low Power Long Rang (LoRa) technology and cellular IoT combined with live video transmission. These integrated protocol yields ultimate results in real time monitoring, lowering the cost of preparation, it could reduce the losing rate of balloon’s payload and also helps the end user to store the data in real time flight operation. The result is achieved over the telemetry health test in a web-based environment.